Self-deception in nonhuman animals: weak crayfish escalated aggression as if they were strong. (13th July 2019) - Angilletta, Michael J; Kubitz, Gregory; Wilson, Robbie S
Abstract: Humans routinely deceive themselves when communicating to others, but no one knows whether other animals do the same. We ask whether dishonest signaling between crayfish meets a condition required for self-deception: dishonest individuals and honest individuals escalate aggression according to their signals of strength rather than actual strength. Using game theory, we predicted how an animal's knowledge of its strength should affect its decision to escalate aggression. At the evolutionary equilibrium, an animal that knows its strength should escalate aggression according to its strength, relative to the expected strength of its opponent. By contrast, an animal that knows only its size should escalate aggression according to its size, relative to the size of its opponent. We tested these predictions by staging encounters between male crayfish ( Cherax dispar ) of known sizes and strengths. Consistent with a model of self-deception, crayfish escalated aggression based on the sizes of their claws relative to those of their opponents, despite the fact that size poorly predicts strength. Males who were weak for their size escalated disputes less often, but their aggression far exceeded the level predicted by a model of self-awareness, suggesting these crayfish were largely ignorant of their deception. Animals that fail to recognize their own dishonest signals may win disputes with stronger opponents without engaging in costly combat. Our game-theoretical approach can be used to identify potential cases of self-deception in nonhuman animals, enabling comparative studies of this behavior. Abstract : Humans routinely overestimate their ability to compete, but no one knows whether other animals engage in this type of self-deception. We used a mathematical model to predict the behavior of crayfish engaging in self-deception. Consistent with our model, weak crayfish behaved as aggressively as strong crayfish, suggesting that they fail to recognize their own strength. Individuals that overestimate their strength can scare away stronger opponents without a fight.